The Introverted Presenter: Ten Steps for Preparing and Delivering Successful Presentations - Tierney, Richard (Springer, 2016)
The introvert is a personality type that draws energy from the outside inward. According to standard personality testing assessments, most people are introverts and no group is more introverted than technical professionals. Introverts are congenitally programmed to recoil from the prospect of public speaking with fear and loathing, yet making presentations to expert and non-expert audiences is an inescapable requirement for career advancement in any technical field. Presentation coach Richard Tierney rides to the rescue of fellow introverts in the IT and engineering sectors with The Introverted Presenter—his fail-safe guide to delivering competent presentations, no matter how unsuited by nature you might be to the performing arts.